ANALISIS SENGKETA HAK ATAS TANAH ULAYAT DI TEMPAT WISATA NEGERI LIANG PERSPEKTIF SOSIOLOGI HUKUM - Lessy, Rauda; Kabakoran, Abubakar; Tuharea, Ismela (IAIN Ambon, 2023)
A conflict or dispute is something that causes a difference of opinion between two or more parties who are disputing a case in court, a social problem that arises because there are differences of opinion or views that occur within the community, and rights, namely ownership and authority according to the law of ulayat land, namely land shared by the people. members of the customary law community concerned. The process of land ownership in the Liang country mostly comes from inheritance from parents and also from the results of buying and selling land, but there are also those who get empty land that is known to have no owner and then use it as their ownership right (parusa). The resolution of conflicts over customary land rights in Liang country tourist attractions is to restore socio-cultural harmony. Liang is a coastal country with a wide expanse of flat land with an average height of 8 meters above sea level. This country is the country with the lowest average altitude in Salahuhtu District. Liang community settlements are on the northeast coast of Ambon Island.Land is an important aspect in human life, land never increases, it can only be moved according to our collective wishes, on the other hand, humans as the most dominant land users always increase at all times.Customary rights are the authority that according to customary law is held by customary law communities over certain areas which constitute the living environment of their residents to take advantage of natural resources including land within the territory. As a result of disputes in the land sector, they can lead to prolonged conflicts between members of the disputing community, even to their heirs, which can cause many victims.